SELECTION AND JUSTIFICATION OF PARAMETERS OF WORKING BODIES OF THE COMBINED TOOLS FOR THE BASIC AND PREPLANT PROCESSING OF SOIL IN THE CULTIVATION OF ROW CROPS IN THE CONDITIONS OF SOUTH KAZAKHSTAN - Rzaliev, A.S.; Bekmuhametov, Sh.B; Goloborodko, V.P. (Academic Journal of Physical and Chemical Sciences, 2021)
. In the southern zone of Kazakhstan, agricultural crops are cultivated, both on irrigated and rain-fed lands. The main technology used for tillage is traditional, which accounts for 90% of all cultivated crops. This technology provides for multiple passes of machine-tractor units (MTU) across the field, which causes a large load on the soil, leading to the destruction of its structure. In the South of the Republic, combined tools supplied from neighboring countries (Russia, Belarus, Ukraine) are mainly used for pre-sowing tillage. They do not correspond to the soil and climate conditions and technologies used. To ensure the required quality of soil preparation, it is necessary to use machines adapted to zonal conditions. To develop a combined tool for pre-sowing and basic tillage, the parameters of its working bodies were justified. Based on the conducted research, a prototype of the combined OKP-4,0 machine was manufactured at the experimental plant of "SPC of agricultural engineering " LLP, and its acceptance tests were carried out during the operation of pre-sowing soil preparation for corn sowing, according to which the quality of soil treatment corresponded to agricultural requirements. There were no breakdowns or failures in operation.